Online Media Trends on Political Party Sentiment Ahead of the 2024 Election in Indonesia - Wiyono Wiyono; Zuly Qodir; Linayati Lestari (Universitas Sultan Ageng Tirtayasa, 2023)
Abstract: The purpose of this study is to find out the tendencies of Indonesian online media on political party sentiment before the 2024 election in Indonesia. Online media is a communication tool for political parties in providing narratives and brief descriptions of the maneuvers of the political parties themselves and the candidates they carry. This study uses a qualitative type, the method used is qualitative data analysis software (QDAS). 72 news documents from detik.com, tribunnews.com, pikiranrakyat.com, and kompas.com as the data sources for this research, news documents published from May to October 2022. Data analysis used the NVivo 12 plus device including sentiment analysis. The results of data analysis show that online media tends towards several political parties in Indonesia, including the tendency of political parties towards their presidential candidates, and five types of sentiment have their nominations. The results of this study state that a very positive type of sentiment is shown in Ganjar Pranowo. In addition, in the four online media, PDI P appears more frequently than the other 8 political parties. However, detik.com tends toward the KIB party, and thoughts of people.com tend toward the democratic party.